The influence of selected socio-demographic factors and the perception of the applied therapy on quality of life of women with breast cancer - Anna Szymczyk; Aneta Gałka; Natalia Świątoniowska; Jagoda Marcinkiewicz (Kazimierz Wielki University, 2018)
Introduction. Breast cancer is the second most common malignancy detected in women in Poland. Every year 14.1% of women die of breast cancer. An important role, among cancer patients, in the treatment process plays their mental attitude, which is related to the perceived satisfaction with life, acceptance of the disease, satisfaction of treatment and coherence. Not without significance is the quality of life, which is considered assessment of the efficacy and safety of therapy. QoL (ang. Quality of life) in cancer depends on the severity and type of the treatment. The aim of the study was to evaluate the influence of selected sociodemographic variables (education, age, marital status, financial situation) and satisfaction with the effects of treatment on quality of life of women with breast cancer. Material and methods. The study involved 150 women with breast cancer. We used a standardized questionnaire EORTC QLQ-C30 to survey a quality of life and own questionnaire. Socio-clinical data have taken from medical records. Results. Older age (r=0.168; p=0.04), good material situation (p=0.004), secondary education level (p=0.041) correlated with better functioning in daily activities. Decreased quality of life in elderly patients was associated with insomnia (r=0.246; p=0.002) as well as financial problems (r=0.166; p=0.043). Patients with primary education level and working have significantly greater financial problems than patients with higher education level (p=0.005). No permanent partner was significantly associated with financial problems (p=0.016), whereas patients that are in a very good financial situation significantly better sexual function compared to patients with good and bad situation (p